EVALUASI EFISIENSI BIAYA DAN WAKTU ANTARA METODE KONVENSIONAL DAN PRACETAK DALAM PEKERJAAN DRAINASE U-DITCH DI RUAS JALAN NASIONAL JAMBI - Iskandar, Bugie Rastapi; Kusmana, Dody (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Sangga Buana, 2024)
Cost and time efficiency are two crucial aspects that influence the success of a construction project. Conventional methods are usually used because they are considered more flexible and easily adapted to field conditions. However, the precast method is increasingly in demand because it is claimed to be more efficient and faster in implementation. This research uses a case study approach by collecting primary and secondary data from planned work. Cost data is obtained from the detailed cost budget (RAB), while time data is taken from the project implementation schedule (time schedule). The analysis was carried out by comparing the total costs and time duration between conventional and precast methods using the 2018 Bina Marga Specifications. The research results show that the precast method has advantages in time efficiency, with an average construction time that is shorter than conventional methods. However, in terms of costs, precast methods tend to be more expensive in the initial stages due to the high production costs of precast elements.